Karakterisasi Parameter Tsunami Terhadap Kepesisiran Pantai Pulau Ternate - Jumaris; Sigit Heru Mukti B.S.; Sudaryatno (Postgraduate, University of Mataram, 2024)
Ternate Island is one of the volcanic islands of the Halmahera volcanic, The Island forms an oceanic region consisting mostly of a unique double subduction tectonic deformation structure. Within this zone, the Moluccas Sea plate subducts beneath the Sangihe and Halmahera volcanic arcs. This research aims to characterise tsunami hazard to Ternate Island. The seismicity data used is combination of seismicity data from earthquake catalog by International Seismological, U.S. Geological Survey, and Meteorology, Climatology and Geophysics Agency during period 1900-2020. The main earthquake data was generated Reasenberg declustering, which previously converted earthquake magnitude for uniformity against catalogue with different data scales into moment magnitude. The tsunami source parameters in the North Maluku Sea area which are generated with a maximum magnitude of 8.5 Mw which can occur in this area are empirically capable of causing dislocations or rupture zones that reach up to 45080 km2 and the equivalent energy released in the form of seismic moments is 7.0795E+21 Nm. The maximum tsunami height at Ternate coast could be up to 3.44 meters.